2006
DOI: 10.1210/jc.2006-0062
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcome of Women with 21-Hydroxylase-Deficient Nonclassic Adrenal Hyperplasia

Abstract: The risk of a mother with 21-OH-deficient NCAH for giving birth to a child affected with CAH is 2.5%; at least 14.8% of children born to these mothers have NCAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
2
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 27 publications
14
121
2
18
Order By: Relevance
“…28 This risk in reality may be higher; a retrospective study of NCCAH women reported a 2.5% risk of a NCCAH woman having a child with classic CAH. 104 When compared to an individual with two normal CYP21A2 alleles, a heterozygote carrier may have slightly elevated 17-OHP levels when stimulated with ACTH, but hormonal testing does not accurately predict the carrier state. Thus, genetic testing is essential to determine the presence of mutations.…”
Section: Genetic Counseling Of Patients With Congenital Adrenal Hypermentioning
confidence: 99%
“…28 This risk in reality may be higher; a retrospective study of NCCAH women reported a 2.5% risk of a NCCAH woman having a child with classic CAH. 104 When compared to an individual with two normal CYP21A2 alleles, a heterozygote carrier may have slightly elevated 17-OHP levels when stimulated with ACTH, but hormonal testing does not accurately predict the carrier state. Thus, genetic testing is essential to determine the presence of mutations.…”
Section: Genetic Counseling Of Patients With Congenital Adrenal Hypermentioning
confidence: 99%
“…Spontaneous miscarriages were more common in the pregnancies prior to NCAH diagnosis [57]. Another series of women with NCAH desiring pregnancy reported similar findings with a decrease in spontaneous miscarriages during glucocorticoid treatment [61].…”
Section: Ovulation Menstruation and Reproductive Functionmentioning
confidence: 70%
“…Moran et al found that the prevalence of 21-OH-deficiency among liveborn children was 2.5% which was higher than the 0.2% calculated prevalence. In addition, at the time of the study 15% of children of mothers with NCAH had been also diagnosed with NCAH [57]. Bidet et al also found the prevalence of CAH to be greater than anticipated [61].…”
Section: Ovulation Menstruation and Reproductive Functionmentioning
confidence: 89%
“…Many women with NCAH are relatively fertile [57, 58]. However, NCAH carries a greater risk of subfertility, in part due to the prevailing ovulatory dysfunction.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In addition, since all “at-risk” fetuses are treated until the definitive diagnosis and chromosomal sex are known, 7/8 fetuses are needlessly exposed to prenatal dexamethasone [100]. Overall, the risk of a patient with NCAH of having a child with CAH is relatively low (2.5%) [57]. Therefore, couples who conceive and whose genetic diagnosis is not known should not be considered for prenatal dexamethasone suppression, unless they have had a prior child with salt-losing or simple virilizing CAH.…”
Section: Treatmentmentioning
confidence: 99%